Comparison of antifungal drugs in the treatment of invasive pulmonary aspergillosis: a systematic review and network meta-analysis - Cheng, Jing; Han, Hedong; Kang, Wenwen; Cai, Zijin; Zhan, Ping; Lv, Tangfeng (Frontiers in Microbiology, 2024)
BackgroundVoriconazole, isavuconazole, and amphotericin (AmB) formulations are currently recommended to treat invasive pulmonary aspergillosis (IPA). We aimed to estimate the efficacy of different antifungal drugs in the initial treatment of IPA.MethodsWe included all available randomized controlled trials (RCTs) evaluating first-line treatments for IPA by searching PubMed, Medline, EMBASE, the Cochrane Library, and the ClinicalTrials.gov database. We performed a network meta-analysis to compare the relative efficacy of different drugs in treating IPA. The primary outcomes were the overall response and all-cause mortality (ACM).ResultsEight studies were identified that compared different drugs including voriconazole, isavuconazole, posaconazole, anidulafungin, liposomal AmB (L-AmB) at standard, high and low doses (3-5 mg/kg/d; 10 mg/kg/d; 1 mg/kg/d), AmB deoxycholate (dAmB) and amphotericin B colloidal dispersion (ABCD). We found that second-generation triazole antifungal drugs containing voriconazole, isavuconazole, and posaconazole exhibited significantly superior overall response to dAmB and ABCD. Voriconazole was ranked as the best drug on network rank analysis. We found no difference in efficacy between triazole antifungals and L-AmB. A combination of voriconazole with anidulafungin, isavuconazole and voriconazole showed significantly better safety than dAmB.ConclusionThe efficacy of second-generation triazole antifungal drugs for the first-line treatment of IPA is comparable with L-AmB and is better than both dAmB and ABCD. Isavuconazole may show better safety than voriconazole and posaconazole. Combination therapy with voriconazole and anidulafungin may serve as an alternative option for IPA patients with limited drug tolerance.Systematic review registrationhttps://inplasy.com/.